POLIGAMI: ANTARA KEBOLEHAN SYARIAT DAN TANTANGAN ETIS ANALISIS MA’ANIL AL HADITS DAN SOSIOLOGI HUKUM - Saifullah; Sutriyono (SAMAWA, 2026)
This article reexamines the meaning and ethical position of polygamy through two approaches: Ma'anil al Hadith and legal sociology. The Ma'anil al Hadith approach emphasizes a meaningful, contextual reading of hadiths that is oriented toward maqāṣid al-syarī'ah, rather than merely textual. Meanwhile, legal sociology analyzes the social function of a norm in modern society. This study finds that polygamy in Islam is not a command or normative preference, but rather a conditional permissibility that arises from a specific socio-historical context. In contemporary social reality, moral conditions, especially inner, psychological, and structural justice, are almost impossible to fulfill. Therefore, polygamy is more accurately understood as a situational rukhṣah, not an ideal family model. This analysis shows that both hadith and modern legal sociology theory lean toward ethical recommendations of monogamy as a form of protection, justice, and family stability. Keywords: Polygamy, Ma’Ani Al-Ḥadis, Sociology of Law, Maqāṣid Al-Syari’Ah, Justice, Modern Family, Prophetic Ethics.